Students’ Knowledge and Perspectives of Using Artificial Intelligence in Academic Writing Works - Yunita, Wisma; Sujarwati, Iis; Dahlia (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
The integration of Artificial Intelligence (AI) tools into the academic writing process has become inevitable. This study aimed to find out the perspectives of the postgraduate (master) students in English education at the Faculty of Teacher Training and Education (henceforth FKIP) at the University of Bengkulu on the use of AI tools in academic writing works. This quantitative survey research involved all postgraduate students of the English Education at FKIP University of Bengkulu in the odd semester of the 2024-2025 academic year, consisting of 60 students as the population and sample of this study. The instrument of the research was a questionnaire adapted from Malik. et al (2023) consisted of 40 closed-ended questions with five Likert Scale (strongly agree, agree, undecided, disagree, and strongly disagree) and given to the respondents using Google Forms. The instrument covered the students’ knowledge of AI in academic writing, the students’ perspective of using artificial intelligence, impact of AI in academic writing works and how AI should collaborate with human writer in the future. The data were analyzed using descriptive quantitative analysis with percentage formula. The results of this study revealed that the postgraduate students of the English Education Study Program at the University of Bengkulu have good knowledge of AI, had a positive perspective of using AI in academic writing work, agree that AI has impact on writing works and agree that AI should collaborate with human writer in the future works.